c.1 - Kohli, Atul (Bombay, 1987)
This analysis of the role of government in eradicating India's rural poverty raises a whole series of crucial contemporary issues relating to the state, its degree of autonomy in the developing world and the problems of effecting genuine redistributive reform. The particular importance of the book is that it focuses attention on the nature of ruling political parties as an important factor influencing the success or failure of redistributive and welfare politics in a democratic-capitalist setting. Dr Kohli compares in detail three state-level Indian governments of the late seventies: Communist-ruled West Bengal, Karnataka under the Congress Party, and Uttar Pradesh under the Janata Party. Comparing these in terms of their success in redistributing agricultural land and creating employment for the rural poor, the author argues cogently that well-organised, left-of-centre parties in government-like that in West Bengal - are the most effective in implementing reform.
Keywords: Poverty